THE EFFECTIVENESS OF SEND A PROBLEM TECHNIQUE FOR TEACHING WRITING AN ANALYTICAL EXPOSITION TEXT (A Quasi-Experimental Study of the Eleventh Grade Students of SMA N 8 Semarang in the Academic Year 2015/2016) - Amilia, Intan Kris; Sisbiyanto, Amir (ELT Forum: Journal of English Language Teaching, 2016)
The aim of the study is to find out whether teaching writing analytical exposition text by using Send a Problem technique is effective or not for Senior High School students. In the working hypothesis (H1), âThere is significant difference in studentsâ writing achievement between those who are taught using Send a Problem and those who are taught using conventional way.â Meanwhile, in the null hypothesis (Ho), âThere is no significant difference in the studentsâ writing achievement between those who are taught using Send a Problem and those who are taught using conventional way.âThe population of this study was the eleventh grade students of SMA Negeri 8 Semarang in the academic year 2015/2016. The total number of the sample was 60 students that consisted of 30 students of class XI IS 4 as the experiment group who were taught using Send a Problem technique and 30 students of class XI IS 5 as the control group who were taught using conventional way. The design of this study was a quasi-experimental study. The data were collected through the writing test. In the pre-test, the mean score of the experimental group was 62.80 and the control group was 62.77. After the treatment, the result of post-test of the experimental group was 75.57 while the control group was 68.57. The independent sample t-test used by the writer showed that there was a significant difference between post-test of control group and experimental group. Lastly, teaching writing analytical exposition text using Send a Problem technique is effective than conventional way. English teachers are suggested to concern better in their technique variety in teaching writing any kind of texts especially analytical exposition text.